The Effect of Motivation and Team Dynamic on Entrepreneurial Learning Success - Raharjo, Tri Joko; ., Harianingsih (KnE Social Sciences, 2019)
The growth of the non-formal education sector in the last decade is indispensable as a form of social services provided by an organization to be a reference for marginalized people to be able to pursue education equivalent to formal education. Entrepreneurship-based learning is an important solution to help and supplement the non-formal education sector to successfully meet many of these challenges. One beneﬁt that is seen in combining entrepreneurship learning systems into non-formal education is the development and improvement of the provided curriculum followed by the conversion of lessons learned into practices and operating principles that help individuals in the organization to maintain and improve their performance capabilities so as to produce graduates who are ready work. Non-formal education is seen as a sustainable resource for learning and improvement not only for individuals in the organizationbutalsoforpartnersandstakeholdersafﬁliatedwithnon-formaleducation. Effective motivation and team dynamics are factors that inﬂuence learning to develop entrepreneurial capacities that are important for the innovation process taken on opportunities that help build and grow non-formal education. There are motivations and dynamics of effective program implementation teams, better strategies, policies, actions, decisions, resource allocations, and many more beneﬁts that will all lead to theabilityofnon-formaleducationtogrowanddevelopandadaptefﬁcientlytochange. Keywords: entrepreneurship based learning, motivation, team dynamic